Perbedaan Asupan Lemak, Karbohidrat dan Pengetahuan Gizi antara Siswa Overweight dan Tidak Overweight di SMK Batik 1 Surakarta - Ramadani, Helen; , Dyah Intan Puspitasari, S.Gz., M.Nutr (2017)
Introduction: Adolescent are the age group which is vulnerable to nutritional problems. During adolescent there are changes in lifestyle and habit of trying newfood. This may cause inadequate intake that leads to overweight. utritional knowledge are also important factors that nfluencing adolescents nutrition. Nutritional problems can be avoided if adolescents have sufficient knowledge about maintaining nutrition intake. The preliminary study onducted at SMK Batik 1 Surakarta found that 19% of students are verweight. Objective: To determine the differences of fats intake, carbohydrates intake and nutritional knowledge between overweight and non overweight students at SMK Batik 1 Surakarta. Methods: The method used is survey with cross sectional design. The research samples were students of class X and XI, which were 40 respondents overweight and 40 respondents non overweight. Data of fat and carbohydrate intake were obtained with 3x24 hour non consecutive food recall. Data of nutrition knowledge were obtained through questionnaire. Data were analyzed by Independent T-Test. Results: The results show that most of fat intake in overweight subjects categorized as high (70%). Most of carbohydrate intake in non overweight in the less category (73%). Most of nutritional knowledge in non overweight subject categorized as sufficient (45%). The p-value of the difference of fat intake between overweight and non overweight subjects was 0.000. Statistical test results of carbohydrate intake differences between overweight and non overweight subjects was p = 0.000. The p-value of the difference of nutritional knowledge between overweight and non overweight subjects was 0.851. Conclusion: There were differences of fat intake and carbohydrate intake between overweight and non overweight subjects. There was no difference between nutrition knowledge between overweight and non overweight subjects. Keywords: fat intake, carbohydrate intake, nutritional knowledge, nutritional status overweight and non overweight.